Makkah Al-Mukarramah in the Pan-Islamic Thought of Jamaluddin Al-Afghani - Spahic, Omer (Hamdard Foundation Pakistan, 2021)
This article discusses the importance of Makkah Al-Mukarramah in the pan-Islamic and reformist thought of Jamaluddin al-Afghani. Afghani framed his ideas within the framework of his calls for universal Islamic unity, brotherhood and cooperation, which - as a result – are examined at the beginning of the article. The article then assesses Afghani’s advocacy that the status of Makkah Al-Mukarramah as the Muslim spiritual qiblah or direction be enriched and expanded into the realms of social relations and intellectual awakening as well, thus also becoming a Muslim emotional, social and intellectual qiblah. As a modus operandi, Afghani put forward the idea of establishing an international network of Muslim scholars, activists and even ordinary people, with Makkah Al-Mukarramah functioning as a nerve centre and its annual hajj season an opportunity for regular conferences. Afghani also suggested that mosques and schools throughout Islamdom be turned into centres of teaching, propagating and facilitating Islamic unity, and that Makkah Al-Mukarramah function as the unifying factor and guidance. Afghani juggled his qualified support for the Ottoman Caliphate with his reformist ideas, some of which went down well neither with the upper political echelons nor some religious leaders in Istanbul. Hence, in order to properly contextualize the pan-Islamic thought of Afghani the article likewise explores the impact of the triad axis of the Ottomans, the caliphate notion and the city of Makkah Al-Mukarramah. The article’s research methodology centres on descriptive as well as analytical qualitative modes, infused with a degree of interdisciplinary leaning.